2018
DOI: 10.1088/1674-1056/27/7/078102
|View full text |Cite
|
Sign up to set email alerts
|

Silica encapsulated ZnO quantum dot-phosphor nanocomposites: Sol-gel preparation and white light-emitting device application

Abstract: ZnO quantum dots (QDs) as an eco-friendly and low-cost material has bright fluorescence, which makes it promising material for healthy lighting and displaying. However, the low fluorescence efficiency and poor stability of ZnO QDs impede their applications in lighting application. In this work, silica encapsulated ZnO QD-phosphors nanocomposites (ZSPN) have been prepared through a sol-gel synthesis process, where yellow-emitting ZnO QDs and blue-emitting BaMgAl 10 O 17 :Eu 2+ are employed as the luminescence c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Very recently, a Chinese research collaboration has made use of silica-containing ZnO quantum dots to fabricate LED phosphors. 166 They used solgel techniques to prepare yellow-emitting silica-encapsulated ZnO quantum dots. The powdered material was then mixed with blue-emitting BaMgAl 10 O 17 ∶Eu 2þ phosphor.…”
Section: Zno Quantum Dot Ledsmentioning
confidence: 99%
“…Very recently, a Chinese research collaboration has made use of silica-containing ZnO quantum dots to fabricate LED phosphors. 166 They used solgel techniques to prepare yellow-emitting silica-encapsulated ZnO quantum dots. The powdered material was then mixed with blue-emitting BaMgAl 10 O 17 ∶Eu 2þ phosphor.…”
Section: Zno Quantum Dot Ledsmentioning
confidence: 99%
“…17 To date, most of the ZnO-WLEDs were realized on the basis of ZnO-QD phosphors that were usually integrated with an ultraviolet or blue excitation source. 25–28 The success of ZnO-QD phosphor WLEDs demonstrated that the ZnO-QD phosphor is a promising material for application in WLEDs. However, the potential risk of backlight leakage in the phosphor WLEDs greatly reduces their practical value because the ultraviolet or blue backlight is harmful to human eyes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to TiO 2 encapsulation, SiO 2 is often used to coat fluorescent nanoparticles for its well-known advantages, such as easy preparation, low toxicity, and excellent light transparency. Additionally, inert SiO 2 layers are able to passivate material surfaces and restrict the rotation and vibration of the bonds, thus coating of SiO 2 can effectively improve the stability and quantum yield of fluorescent nanoparticles. , Hu et al prepared monodisperse PQDs/SiO 2 Janus nanoparticles using an interfacial synthesis method and used the stabilized PQDs for fabricating white light LED devices . In the PQDs/SiO 2 Janus particles, single PQD nanocubes were protected by SiO 2 only at one side; thus, it was still difficult to apply them in aqueous environments usually met in bioimaging and chemical sensing.…”
Section: Introductionmentioning
confidence: 99%